One glorious ambition [large type] : the compassionate crusade of Dorothea Dix - Kirkpatrick, Jane, 1946- (Center Point Large Print, 2013)
Born to an unavailable mother and an abusive father, Dorothea Dix longs simply to protect and care for her younger brothers, Charles and Joseph. But at just fourteen, she is separated from them and sent to live with relatives to be raised properly. Lonely and uncertain, Dorothea discovers that she does not possess the ability to accept the social expectations imposed on her gender and she desires to accomplish something more than finding a suitable mate.